PENGEMBANGAN DESAIN MODEL PELATIHAN KEPEMIMPINAN KEPALA SEKOLAH BERBASIS NILAI-NILAI KEARIFAN LOKAL - Yohanes Harsoyo; Catharina Wigati Retno Astusi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
School leadership is a key factor in school management. The reality on the ground shows that preparing for principal is less than adequate. Therefore, it isnecessary to think about the principal's training model that can really preparethe principal so that the principal has the required competencies. During thistime the characteristics of effective school leadership more refer to the resultsof research and literature or foreign text. This is not bad. However, it isnecessary to develop leadership training modelsthat are based on local wisdomvalues.This study aims to produce a description of the problems and needs in schoolleadership and the values of local wisdom that are considered relevant to theleadership of the school. The survey was conducted on 28 principals fromYogyakarta, Central Java, and East Java.This study produces important conclusions that are (1) the order of difficultylevel of competence from the most difficult to the easiest, namely managerialcompetence, entrepreneurial competence, supervision competence, competenceto translate school values, personality competence, and social competence. and(2) are the three order of popularity of leadership values according toprincipals are Asta Brata, Among System, and Sastra Gendhing. Keywords: training model, leadership, principal, and local wisdom